Af`al Allah Menurut Ahl al-Sunnah wa al-Jama`ah: The Attributes of Allah according to Ahl al-Sunnah wa al-Jama`ah - Ismail, Mohd Hamidi; Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2015)
The attributes of Allah is one of the most important topic debated in Islamic faith. This was based on its importance how to relate neoteric subject that is human with ancient one who is Allah the Almighty as it was described and understood through the sixth pillar of faith in Islam which is belief in qada’ wa qadar (judgment and predestine) of Allah the Almighty. Generally, debating on the attributes of Allah cannot be avoided from polemical matter. It is obvious, not just referring to the argumentative by scholars from various Islamic schools of thought even by the same school which is Ahl al-Sunnah wa al-Jama‘ah. Describing the polemical aspect on the attributes of Allah from their perspective, this article will elaborate how we cannot find any polemic causing separation and exile as we found it from debatable in the same issue – the attributes of Allah – between other Islamic schools of thought. Even, what we will find is compatibility and intimacy in methodical and understanding. This article formulated the disagreement is in context of pronunciational and not contextual which can caused discrepant in understanding in Ahl al-Sunnah wa al-Jama‘ah’s school of thought when Asharite and Maturidis agree in creating connection between Allah and human through medium that can suit attributes of Allah with human which recognized by Asha rite as al-ta‘alluq and by Maturidis as al-takwin.